2021
DOI: 10.1042/cs20200306
|View full text |Cite
|
Sign up to set email alerts
|

Clonal haematopoiesis of indeterminate potential: intersections between inflammation, vascular disease and heart failure

Abstract: Ageing is a major risk factor for the development of cardiovascular disease (CVD) and cancer. Whilst the cumulative effect of exposure to conventional cardiovascular risk factors is important, recent evidence highlights clonal haematopoiesis of indeterminant potential (CHIP) as a further key risk factor. CHIP reflects the accumulation of somatic, potentially pro-leukaemic gene mutations within haematopoietic stem cells over time. The most common mutations associated with CHIP and CVD occur in genes that also p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 157 publications
0
23
0
Order By: Relevance
“…However, aging leads to their exhaustion resulting in lower capacity for self-renewal and deterioration of their differentiation ability, with significant consequences on both adaptive and innate immunity. Furthermore, with age, HSCs accumulate mutagenic events, which lead to positive selection and outgrowth of selected clones ( Khetarpal et al, 2019 ; Mooney et al, 2021 ). The presence of clonal mutant stem cells without the development of overt hematologic malignancy and other clonal diseases is referred to as clonal hematopoiesis of indeterminate potential (CHIP) (Tyrrell and Goldstein, 2021 ; Libby and Ebert, 2018 ; Khetarpal et al, 2019 ).…”
Section: Molecular Determinants Of Inflamm-agingmentioning
confidence: 99%
See 2 more Smart Citations
“…However, aging leads to their exhaustion resulting in lower capacity for self-renewal and deterioration of their differentiation ability, with significant consequences on both adaptive and innate immunity. Furthermore, with age, HSCs accumulate mutagenic events, which lead to positive selection and outgrowth of selected clones ( Khetarpal et al, 2019 ; Mooney et al, 2021 ). The presence of clonal mutant stem cells without the development of overt hematologic malignancy and other clonal diseases is referred to as clonal hematopoiesis of indeterminate potential (CHIP) (Tyrrell and Goldstein, 2021 ; Libby and Ebert, 2018 ; Khetarpal et al, 2019 ).…”
Section: Molecular Determinants Of Inflamm-agingmentioning
confidence: 99%
“…The presence of clonal mutant stem cells without the development of overt hematologic malignancy and other clonal diseases is referred to as clonal hematopoiesis of indeterminate potential (CHIP) (Tyrrell and Goldstein, 2021 ; Libby and Ebert, 2018 ; Khetarpal et al, 2019 ). The most frequently encountered mutated genes in CHIP are DNA methyltransferase 3 (DNMT3A), ten-eleven-translocation 1 (TET2), Janus kinase 2 (Jak2), and additional sex comb-like 1 (ASXL1) ( Jaiswal et al, 2014 ; Mooney et al, 2021 ). A cross-sectional study reported that the frequency of clonal somatic mutations in peripheral blood cells increases with age, reaching a prevalence of around 10% in individuals above 70 years, whereas they are rarely found in younger individuals ( Jaiswal et al, 2014 ).…”
Section: Molecular Determinants Of Inflamm-agingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based upon next generation DNA sequencing (NGS) data, approximately 15–20% of people of age 70 or older carry a detectable cancer-associated somatic mutation at ≥2% variant allele frequency within known driver genes in a substantial proportion of their blood cells. This phenomenon, known as clonal hematopoiesis of indeterminate potential (CHIP), occurs most commonly as a result of mutations in the transcriptional regulators DNMT3A, TET2 and ASXL1 ( Link and Walter, 2016 ; Bejar, 2017 ; Jaiswal and Ebert, 2019 ; Libby et al, 2019 ; Mooney et al, 2021 ). Understandably, individuals with CHIP display modestly increased risk of developing a hematologic malignancy, although the vast majority of individuals with this condition do not develop blood cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Cardiovascular-Oncology is now well-established as a clinical specialty and is receiving an appropriate increase in attention from the pre-clinical scientific community. Patients with cancer are more prone to cardiovascular comorbidity as a result of shared genetic predispositions [ 1 , 2 ] and risk factors including smoking, obesity and inflammation [ 2 ]. Furthermore, this heightened risk for cardiovascular disease may be further amplified by cancer therapies because of overlap between pathways required for normal cardiovascular homoeostasis and those involved in tumour initiation, growth and metastasis.…”
mentioning
confidence: 99%